Rethinking commerce education in South Africa - Loots, Elsabé (AOSIS, 2024)
This book aims to advance the knowledge on the future of business education in South Africa and to allow all relevant role players (universities and industry) the opportunity to debate and share ideas on how to best position business education to optimally serve the interest of students and the dynamic changes taking place in the world of work. Although some of these changes have taken shape before 2020, the COVID-19 pandemic has accelerated the need and pace for change. If business schools (in our context, faculties of economic and management sciences) do not adapt rapidly, they will be left behind by other up-and-coming industry providers. The research scope covers all business-related undergraduate and postgraduate economics, management and accounting programmes, excluding MBA programmes.